2017
DOI: 10.1002/ps.4504
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, fecundity and development among bed bugs (Cimex lectularius) exposed to prolonged, intermediate cold stress

Abstract: BACKGROUNDBed bugs (Cimex lectularius L.) have returned as a nuisance pest worldwide. Their ability to withstand different types of environmental stress should be explored in order potentially to increase the efficiency of control methods.RESULTSImmediate and long‐term effects of exposure to temperatures from 0 to −10 °C for 1, 2 and 3 weeks are reported. Fifth‐instar nymphs and adults were exposed to constant or fluctuating temperatures. Increased cold and extended time yielded higher mortality; nymphs were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This finding demonstrates the need for studies of the long-term effects from sublethal stressors, and the complexity of the mechanisms is further highlighted by the different responses at both ends of the temperature scale. Sublethal cold exposure affects adult bed bugs, but this is not sustained in their later offspring [ 35 ], whereas heat enforces both direct and cross-generational effects [ 40 ] to cause a prolonged detrimental population impact. These differentiated effects may be a further indication of Wolbachia regulated responses to heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…This finding demonstrates the need for studies of the long-term effects from sublethal stressors, and the complexity of the mechanisms is further highlighted by the different responses at both ends of the temperature scale. Sublethal cold exposure affects adult bed bugs, but this is not sustained in their later offspring [ 35 ], whereas heat enforces both direct and cross-generational effects [ 40 ] to cause a prolonged detrimental population impact. These differentiated effects may be a further indication of Wolbachia regulated responses to heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of cold exposure depend on both the severity and duration of the exposure. These factors interact such that prolonged exposure to mild cold stress elicits fitness consequences similar to acute exposure to severe cold stress (Marshall & Sinclair, ; Overgaard & Macmillan, ; Rukke et al, ; Teets & Denlinger, ). Here we found that prolonged exposure to moderate cold increased risk of mortality and resulted in deficits in locomotor behavior in a dose‐ and sex‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…L. Andersen et al, 2015;Kellermann et al, 2012). This thermal tolerance/range distribution relationship is mediated by the fitness consequences of cold exposure, which include reduced fecundity (Marshall & Sinclair, 2010;Rinehart, Yocum, & Denlinger, 2000), developmental defects (Rukke, Hage, & Aak, 2017), and risk of mortality from cold injury (Colinet, Lee, & Hoffmann, 2010;MacMillan & Sinclair, 2011;Renault, 2011;Teets & Denlinger, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such acute exposures to CT min are non‐lethal. Other assays measure survival duration after a sudden drop to a fixed T b (e.g., Heatwole et al ., 1969; Gregory, 1982; Burke et al ., 2002; Storey, 2006; Olson et al ., 2013; Rukke et al ., 2016; but see Huang and Tu, 2008; Berman et al ., 2016), freezing temperature (Lowe et al ., 1971) or super‐cooling temperature (Lowe et al ., 1971; Storey, 2006). Exposure to freezing or supercooling temperatures for a few hours or day is typically lethal (Storey, 2006; but see Costanzo et al ., 1995; Berman et al ., 2016), but whether prolonged exposure to cold but above‐freezing temperatures is lethal is unclear.…”
Section: Question I Which Depth Minimizes Risk Of Cold Injury or Death?mentioning
confidence: 99%